2017
DOI: 10.7567/jjap.56.070304
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of (0001) and $(000\bar{1})$ GaN metalorganic vapor phase epitaxy

Abstract: We performed a thermodynamic analysis of GaN metalorganic vapor phase epitaxy considering the (0001) and surface states. Surface reconstruction, which depends on growth conditions such as temperature and partial pressure, affects growth processes. To discuss the effects of surface states on growth processes, we investigated the driving force of precursor deposition to form the surface phase defined stoichiometrically. In both N2 and H2 carrier gas cases, we showed surface phase diagrams, calculated driving fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 20 publications
(27 reference statements)
0
30
0
Order By: Relevance
“…In addition, the emergence of the polar (0001) plateau remarkably depends on carrier gas. As the driving force on (0001) surface for H 2 carrier gas is different from that for N 2 carrier gas, the differences in the driving force between the semipolar and (0001) surfaces depending on carrier gas are seen in the growth temperatures of GaN MOVPE. Consequently, the effect of driving force on various surface orientations under H 2 carrier gas condition is more remarkable than that under N 2 carrier gas condition around 800–1100 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the emergence of the polar (0001) plateau remarkably depends on carrier gas. As the driving force on (0001) surface for H 2 carrier gas is different from that for N 2 carrier gas, the differences in the driving force between the semipolar and (0001) surfaces depending on carrier gas are seen in the growth temperatures of GaN MOVPE. Consequently, the effect of driving force on various surface orientations under H 2 carrier gas condition is more remarkable than that under N 2 carrier gas condition around 800–1100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is well known that the MOVPE condition, such as growth temperature, partial pressure, and carrier gas, is crucial for the equilibrium crystal shape in GaN nanostructures. In this study, these parameters are taken into account by constructing surface phase diagrams among various orientations as functions of growth temperature and partial pressure …”
Section: Computational Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001, Kangawa et al proposed a theoretical approach for creating a surface phase diagram using the chemical potentials of molecules as functions of the temperature and partial pressures [7]. To date, reconstructed structures for polar, non-polar, and semi-polar GaN surfaces during the growth process have been studied [8,9,10,11,12,13,14,15,16,17,18,19]. Kusaba et al reported the Ga adatom surface and the 3Ga-H surface for (0001) and the 3N-H surface for (000−1) appear for typical GaN MOVPE conditions [19].…”
Section: Adsorption Structurementioning
confidence: 99%
“…The growth conditions are set as follows: pGa=2.5×104 atm and pcarrier=pN2+pH2=0.7 atm, which means that the V/III ratio, pNH3/pGa, is set at 1200. The details of the structures of candidate reconstructed surfaces are provided in Reference [19]. In the case of GaN(0001) growth, a hydrogen adsorbed surface, 3Ga-H (2 × 2), appears at a H 2 partial pressure greater than about 0.5 atm and around a typical growth temperature of 1050 °C.…”
Section: Adsorption Structurementioning
confidence: 99%